From Ambivalence to Betrayal : The Left, the Jews, and Israel - Wistrich, Robert S., 1945-2015 (Book collections on Project MUSE., 2012)
From Ambivalence to Betrayal is the first study to explore the transformation in attitudes on the Left toward the Jews, Zionism, and Israel since the origins of European socialism in the 1840s until the present. This pathbreaking synthesis reveals a striking continuity in negative stereotypes of Jews, contempt for Judaism, and negation of Jewish national self-determination from the days of Karl Marx to the current left-wing intellectual assault on Israel. World-renowned expert on the history of antisemitism Robert S. Wistrich provides not only a powerful analysis of how and why the Left emerged as a spearhead of anti-Israel sentiment but also new insights into the wider involvement of Jews in radical movements. There are fascinating portraits of Marx, Moses Hess, Bernard Lazare, Rosa Luxemburg, Leon Trotsky, and other Jewish intellectuals, alongside analyses of the darker face of socialist and Communist antisemitism. The closing section eloquently exposes the degeneration of leftist anti-Zionist critiques into a novel form of "anti-racist" racism